Sexual Conflict and Gender Gap Effects: Associations between Social Context and Sex on Rated Attractiveness and Economic Status - Gouda-Vossos, Amany; Dixson, Barnaby J.; Brooks, Robert C. (PLOS ONE, 2016)
Human mate choice research often concerns sex differences in the importance of traits such as physical attractiveness and social status. A growing number of studies indicate that cues to social context, including other people who appear in stimulus photographs, can alter that individual’s attractiveness. Fewer studies, however, consider judgements of traits other than physical attractiveness, such as wealth. Here we manipulate the presence/absence of other people in photographs of target models, and test the effects on judgments of both attractiveness and earnings (a proxy for status). Participants (N = 2044) rated either male or female models for either physical attractiveness or social/economic status when presented alone, with same sex others or with opposite sex others. We collectively refer to this manipulation as ‘social context’. Male and female models received similar responses for physical attractiveness, but social context affected ratings of status differently for women and men. Males presented alongside other men received the highest status ratings while females presented alone were given the highest status ratings. Further, the status of females presented alongside a male was constrained by the rated status of that male. Our results suggests that high status may not directly lead to high attractiveness in men, but that status is more readily attributed to men than to women. This divide in status between the sexes is very clear when men and women are presented together, possibly reflecting one underlying mechanism of the modern day gender gap and sexist attitudes to women’s economic participation. This adds complexity to our understanding of the relationship between attractiveness, status, and sex in the light of parental investment theory, sexual conflict and economic theory.